Audience engagement in practice tests and instructional videos on YouTube - Ikanubun, Lucia Ekawati; Iwo, Lidiah Tereda (Jurnal Inovasi Teknologi Pendidikan, 2025)
As a digital video-sharing platform, YouTube has vast resources for sharing educational content. It is an accessible, open educational resource to assist the audience in gaining information and knowledge for educational needs. The research explored audience engagement and viewing patterns between two types of educational videos- instructional videos and practice test videos on a single Indonesian educational YouTube channel. It employed a quantitative descriptive approach to identify audience engagement and viewing patterns for both categories of videos. The data is collected through YouTube analytics with a population of 218 educational videos. The sample used is 139 videos chosen from the two video categories using proportional random sampling, ensuring each category is represented. The finding reveals that instructional videos have high numbers in view and shares metrics, while practice test videos topped in likes, watching duration, and average view duration metrics. This research provides insight to teachers, educational content creators, and those involved in the educational field, optimizing content strategy for digital learning resources in video formats. Further research can explore audiences' motivations for watching educational content and other metrics related to watching long or short videos that can affect audience engagement, which can provide broader insights regarding learning preferences in online video platforms.